Late Miocene eastwards transatlantic dispersal of flightless anchonine weevils (Coleoptera: Curculionidae: Molytinae) - Grebennikov, Vasily V.; Anderson, Robert S. (Zootaxa, 2021)
The weevil genera Aethiopacorep Voisin and Titilayo Cristóvão & Lyal are the only native African members of the nearly pantropical and poorly known tribe Anchonini. All Anchonini are flightless, a trait likely limiting dispersal, yet these weevils are found on both sides of the Atlantic Ocean. A phylogenetic analysis of 79 terminals and 3248 aligned positions from one mitochondrial and two nuclear ribosomal fragments supports a clade of West African Anchonini nested within American Anchonini. As suggested by previous authors, the Asian genera Himalanchonus Zherikhin and Otibazo Morimoto do not form a clade with the tribe’s core, and along with Cycloterinus Kolbe, Euthycodes Pascoe, Leptanchonus Morimoto, Nepalanchonus Zherikhin, and Tanyomus Champion, are here removed from Anchonini and placed as Molytinae incertae sedis. So defined, the monophyletic tribe Anchonini contains 36 genus-group names, all but two denoting American taxa. Using molecular clock analysis, we estimate the separation of the West African Anchonini from its American sister at 9.5–5.2 million years ago (Ma). This date greatly postdates the Cretaceous opening of the Atlantic Ocean (about 100 Ma) and, therefore, evokes a single transatlantic dispersal to West Africa, likely by over-water rafting, leading to subsequent diversification. We postulate this to be the first documented eastwards crossing of the Atlantic Ocean by terrestrial non-volant arthropods based on morphological and molecular data.